A review of the scorpionflies (Mecoptera) of Indochina with the description of a new species of Neopanorpa from Northern Thailand - Bicha, Wesley J. (Zootaxa, 2010)
Thirty-nine species of scorpionflies are currently known from Indochina, consisting of 34 Neopanorpa, 1 Panorpa, and one, and 1 Bicaubittacus. An additional new species from northern Thailand, Neopanorpa latiseparata, is described and illustrated, and its biology is discussed. The male of this species has a wide subquadrate separation between the hypovalves of sternum 9. Additional distribution and seasonal data for Indochinese Mecoptera are provided.